1998
DOI: 10.1523/jneurosci.18-05-01841.1998
|View full text |Cite
|
Sign up to set email alerts
|

Successful Verbal Encoding into Episodic Memory Engages the Posterior Hippocampus: A Parametrically Analyzed Functional Magnetic Resonance Imaging Study

Abstract: The medial temporal lobe (MTL) is essential for episodic memory encoding, as evidenced by memory deficits in patients with MTL damage. However, previous functional neuroimaging studies have either failed to show MTL activation during encoding or they did not differentiate between two MTL related processes: novelty assessment and episodic memory encoding. Furthermore, there is evidence that the MTL can be subdivided into subcomponents serving different memory processes, but the extent of this functional subdivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
146
4
3

Year Published

1998
1998
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 228 publications
(188 citation statements)
references
References 58 publications
32
146
4
3
Order By: Relevance
“…One possible way of interpreting these data is that the suggested age-related rCBF changes observed with PET indicate an age-related encoding failure. In this PET study of upper middleaged/older illiterate women, effective episodic encoding correlated with the activity in the PFC and the MTL regions similar to the observations in young study populations (Alkire et al, 1998;Brewer et al, 1998;Fernandez et al, 1998;Wagner et al, 1998c). In our previous PET study of the literate group (Petersson et al, 1998a) we found no obvious differences in the activation pattern during either encoding or retrieval compared to the activation patterns described in younger populations (Buckner, 1996;Cabeza and Nyberg, 1997a;Fletcher et al, 1997).…”
Section: Pet Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…One possible way of interpreting these data is that the suggested age-related rCBF changes observed with PET indicate an age-related encoding failure. In this PET study of upper middleaged/older illiterate women, effective episodic encoding correlated with the activity in the PFC and the MTL regions similar to the observations in young study populations (Alkire et al, 1998;Brewer et al, 1998;Fernandez et al, 1998;Wagner et al, 1998c). In our previous PET study of the literate group (Petersson et al, 1998a) we found no obvious differences in the activation pattern during either encoding or retrieval compared to the activation patterns described in younger populations (Buckner, 1996;Cabeza and Nyberg, 1997a;Fletcher et al, 1997).…”
Section: Pet Resultssupporting
confidence: 85%
“…Both these studies used well-educated college students. Similar results, using young subjects (mean age 25), in a metabolic FDG-PET study (Alkire et al, 1998) and a blocked FMRI study (Fernandez et al, 1998) also indicate that effective encoding is related to increased MTL activation. Since long-term memory processes are thought to be general purpose mechanisms, it is important that these results are replicated in other study populations.…”
Section: Pet Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…With declarative memory paradigms that activate the medial temporal lobe limbic structures, interest has focused on the significance of anterior vs. posterior, right vs. left-sided, and hippocampal vs. parahippocampal activation patterns (Dolan and Fletcher, 1999;Fernandez et al, 1998;Grady et al, 1995;Haxby et al, 1996;Kelley et al, 1998;Rombouts et al, 1997;Stern et al, 1996;Wagner et al, 1998). Task specific differences in the anatomic distribution of fMRI activation, when averaged across subjects, have been cited as proof of functional specialization of different brain areas.…”
Section: Introductionmentioning
confidence: 99%